Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille